Dor de origem dentária e fatores associados: um estudo de base populacional em adultos - Pelotas, RS, 2005. - Bastos, João Luiz Dornelles (2006)
The aim of this study was to estimate toothache prevalence and associated factors among adult residents in a Southern Brazilian city, named Pelotas. A cross-sectional population-based study was carried out with individuals aged 20 years and over (n=3353). A multi-stage sampling scheme was adopted, and data collection was performed at participants homes through standardised pre-tested questionnaires. Toothache in the past six months was regarded as the outcome. Socio-economic and demographic data as well as health related behaviours were collected. All analyses were undertaken with a Poisson regression model, following a hierarchical conceptual model. The response rate was 93.5% and toothache prevalence was 17.7% (CI95% 16.0-19.3). Multivariable analyses revealed that toothache was more likely to be reported by those with low educational attainment and low family income. Younger subjects, women and those with black skin colour were also more likely to report toothache. Current smokers and problem drinkers were at increased risk of experiencing toothache in the past six months. The toothache prevalence reported in the present study is not negligible and should stimulate preventive policies and support the planning of local oral health services.